From Entertainment to Critique: Violence and Politics in Video Game Art - Martins, Carmem (Revista do Colóquio, 2026)
This article analyzes works by Harun Farocki, Wafaa Bilal, and Joseph DeLappe that explore the relationship between video games and violence. Through a critical analysis of these works, the study investigates how these artists appropriate video game imagery and mechanisms. The findings reveal the construction of a metalanguage that highlights the role of these images in shaping contemporary reality. The article concludes that such artistic practices repurpose technologies associated with military use, transforming them into instruments of political and aesthetic critique.
Keywords: video games; violence; war; video game art; digital art